The Role Of Internal Communication And Incentives And Bonuses In Improving Organizational Commitment "A Field Study In General Commission For Al-Ghab Administration And Development" (Latakia University Journal - Economic and Legal Sciences Series, 2020)
This research aimed at determining The Role of Internal Communication, Incentives and Bonuses in Improving Organizational Commitment at General Commission for Al-Ghab Administration and Development. The researcher relied on the methodological approach as a general approach to research, followed the methodology of the survey, and a set of methods, including relying on secondary and primary data through a questionnaire that was organized by the researcher's knowledge of published literature.He distributed the questionnaire to 333 individuals from workers in the first, second and third category in the Commission, 270 of which were recovered, and 10 were not valid for analysis in the research community comprised of permanent staff in the three categories, of the 2488 respondents according to statistics of the Commission, and then used the appropriate statistical tests, such as simple regression, and rely on a programme SPSS is applied to be a tool for analysis of Data available. The main conclusion was a moral role, a strong correlation between internal communication and improving organizational Commitment, and an Acceptable correlation between, incentives and bonuses and improving organizational Commitment.Some suggestions and recommendations were presented to improve the relationship, which is the most important: the need to work for improvement of the internal communication system and Continue to give incentives and bonuses.